Implementasi Tapping-Box Pada Pajak Parkir Kota Pekanbaru - Sisis Aurela; Mimin Sundari Nasution (Peneliti.net, 2022)
The smooth process of tax reporting cannot be separated from the supervision of the Pekanbaru City Regional Revenue Agency. Efforts made by the Regional Revenue Agency of Pekanbaru City is to implement a tapping-box. This tapping box functions as a transaction recording device where the data will be sent directly to the Regional Revenue Agency server. However, there are still many parking taxpayers who do not install the tapping-box due to the incompatibility of the taxpayer system with the tapping-box system so that it cannot be connected. This research was conducted using qualitative research theory. Using George Edward III's Policy Implementation theory, namely communication, resources, disposition and bureaucratic structure. The technique used to select informants in this research is purposive sampling technique. Data collection is done by interview and documentation. Then the data obtained were analyzed by analysis of the model from Miles and Hubberman. The purpose of this study is to find out how the Tapping-Box Implementation of Pekanbaru City Parking Tax as a supervisory function. The implementation of the tapping-box on the parking tax has not been implemented optimally, which can be seen from the inhibiting factor, namely the implementation of the Pekanbaru City Parking Tax Tapping-Box, namely the incompatibility of the system owned by parking taxpayers with the tapping-box system so that the tapping-box cannot be connected to devices from parking taxpayers and vulnerable to network stability.